Recent trends in incidence, geographical distribution, and survival of papillary thyroid cancer in France. Issue 4 (August 2015) - Colonna, M.; Uhry, Z.; Guizard, AV.; Delafosse, P.; Schvartz, C.; Belot, A.; Grosclaude, P.; the FRANCIM network
Highlights Time trend analysis of papillary thyroid cancer showed a dramatic increase. This increase has slowed down within in recent years, especially at younger ages. There is a strong geographic disparity in incidence between areas in France. 10-years net survival is high and has improved between 1989 and 2004.